Sosialisasi Pentingnya Pencatatan Keuangan Digital bagi Generasi Z yang Memulai Bisnis Online - Liswanty, Ina; Masyitah, Emi; Rizki, Santi; Daifiria, Daifiria; Lazuli, Ivi (Publikasi Pengabdian Masyarakat, 2024)
Generation Z, as a tech-savvy generation, has a strong interest in starting online businesses. However, many of them lack an understanding of the importance of financial record-keeping in running a business. This community service activity aims to provide socialization on the importance of digital financial record-keeping for Generation Z who are starting online businesses. The methods used include delivering theoretical material, demonstrating digital financial tools, hands-on practice, and interactive discussions. Participants were introduced to digital financial applications such as Accurate and taught how to record transactions, prepare simple financial reports, and understand the basics of taxation. The activity was held on November 2, 2025, from 09:00 AM to 12:00 PM Western Indonesia Time (WIB), attended by approximately 100 Generation Z online business actors. Evaluation results showed that 90% of participants found the material relevant to their needs, and 85% were able to use digital financial tools after the training. This activity successfully improved participants' understanding and skills in managing online business finances, as well as raised awareness of the importance of proper financial record-keeping. The positive impact of this activity was felt not only by the participants but also by the online businesses they run, the surrounding community, and the organizing institution. Thus, this activity has made a significant contribution to improving financial literacy and entrepreneurship among Generation Z.